ответ: 150
Объяснение:
выносим 3 за скобки
3а^2-3b^2=3(а^2-b^2)
Затем пользуемся формулой а^2-b^2=(a+b)(a-b)
3(а^2-b^2)=3(a+b)(a-b)
Затем подставляем нужные значения
3(a+b)(a-b)=3(7.5+2.5)(7.5-2.5)=3*10*5=150
В итоге записываем так:
3а^2-3b^2=3(а^2-b^2)=3(a+b)(a-b)=3(7.5+2.5)(7.5-2.5)=3*10*5=150
ответ: 150
Объяснение:
выносим 3 за скобки
3а^2-3b^2=3(а^2-b^2)
Затем пользуемся формулой а^2-b^2=(a+b)(a-b)
3(а^2-b^2)=3(a+b)(a-b)
Затем подставляем нужные значения
3(a+b)(a-b)=3(7.5+2.5)(7.5-2.5)=3*10*5=150
В итоге записываем так:
3а^2-3b^2=3(а^2-b^2)=3(a+b)(a-b)=3(7.5+2.5)(7.5-2.5)=3*10*5=150